Estudo sobre as aplicações de tratamento da Baccharis dracunculifolia em um modelo de estresse crônico variado em ratos - Freitas, Samarah Perszel de (2015)
This study looked at the effects of administration of Baccharis dracunculifolia extract on behavioral, morphological and biochemical parameters in rats submitted to a model of chronic variable stress. The study used 60 Wistar rats, which were 90-day aged in the beginning of the experiment. The animals were equally and randomically divided in 5 groups: Control (Ct); Control Baccharis dracunculifolia (CBD); Chronic stress (Ec): Chronic stress + Baccharis dracunculifolia 100mg / kg (Ec / BD - 100); Chronic stress + Baccharis dracunculifolia 200mg / kg (Ec / BD - 200); Chronic stress + Baccharis dracunculifolia 400mg / kg (Ec / BD - 400). The animals were exposed to stress for a period of 40 days. In this period, one stressor was chosen daily and randomically between the followings: cold exposure, immobilization, the tilt-housing box, flashing light, food deprivation, forced swimming and absence of shavings exchange. After the last stress session, the animals were submitted to the followings behavioral tasks: elevated plus maze, open field task, measurement of palatable food intake, radial arm maze. The day after the last behavioral task session, the animals were euthanized through decapitation. Trunk blood was collected for biochemical analysis (glucose, cholesterol, triglycerides and corticosterone). Heart, adipose tissue (mesenteric, retroperitoneal and periepididymal fat), left kidney and left adrenal gland were weighed. Also, it was performed histological analysis of the heart, left adrenal and left hippocampus. The results showed that the Ec group obtained the highest time spent in the closed arms, which features anhedonia. These results indicate that Baccharis dracunculifolia reversed anxious and anhedonic behavior in animals. The first to the third day of training for feeding behavior task, groups submitted to stress consumed more sweet food than the control group. During the 1st and 2nd weeks, the animals submitted or not to stress showed no differences in dietary patterns. Between 3rd and 8th weeks that followed the experiment, there were changes in both the gross weight of the animals and the Lee index. Concerning the biochemical parameters it can be seen that corticosterone levels in animals Ec and Ec / 400 was significantly higher than the other groups. The Baccharis dracunculifolia also seems to facilitate the learning process and improves performance in the reference memory tasks. There was a significant increase in systolic and average pressure in the Ec group. This study showed that Baccharis dracunculifolia provides benefits of both mnemonic activities, as the plant seems to facilitate the learning process, and its cardioprotective effect. However, more studies are needed to better understand the benefits of Baccharis dracunculifolia and the processes involved in chronic stress.